POLYCYCLIC AROMATIC HYDROCARBONS, THEIR URINARY METABOLITES AND HEALTH - Radosavljevic, Vladan (HEALTH CARE, 2021)
The World Health Organization (WHO) stated as one of its conclusions that air pollution is a leading environmental health risk. Polycyclic aromatic hydrocarbons (PAHs) are well-known carcinogens (above five hundred compounds) that cause lung and skin cancer, especially in occupationally exposed workers. By significantly reducing emissions from modern combustion plants, traffic control, and strict smoking bans in public places, PAHs exposure can be reduced. PAH exposure ought to be better investigated, especially in the field of mass biomonitoring of the urinary concentrations of their major metabolites. Such biomonitoring ought to integrate exposures to chemical carcinogens from different sources (air, water, food, consumer products, professional procedures, etc.), as well as exposure to chemical noxae through the respiratory tract by (inhalation), digestive tract (ingestion), or through the skin. Analysis of the concentration of main PAHs metabolites in urine must be done with highly sophisticated equipment for a valid database to be obtained. The data thus obtained are necessary for risk assessment and health policymaking in order to reduce exposure to chemical carcinogens.